2019
DOI: 10.1055/a-0869-8053
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Concentration of C-reactive Protein is Correlated to Increased Concentrations of Quetiapine, But Not of Risperidone, Olanzapine and Aripiprazole in a Naturalistic Setting

Abstract: Introduction Infections can alter drug clearance, but the impact of inflammation-induced changes is still not well known. The aim of the investigation was to examine the effect of pathological C-reactive protein (CRP) values (≥0.5 mg/dL) and leukocyte count on the metabolism of 4 different atypical antipsychotics. Methods Steady-state serum concentrations of individual patients under therapy with risperidone (n=45), aripiprazole (n=30), olanzapine (n=24), and quetiapine (n=166) were retrospectively analyzed du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The studies of changes in BDNF levels during treatment are controversial; only relapse schizophrenic males patients showed elevated BDNF after 4 weeks of risperidone consumption (3-6 mg/day), a result that suggests gender should be considered when choosing the pharmacological treatment (167)(168)(169). However, other studies reported no alteration whatsoever after risperidone consumption (170,171).…”
Section: Risperidonementioning
confidence: 99%
“…The studies of changes in BDNF levels during treatment are controversial; only relapse schizophrenic males patients showed elevated BDNF after 4 weeks of risperidone consumption (3-6 mg/day), a result that suggests gender should be considered when choosing the pharmacological treatment (167)(168)(169). However, other studies reported no alteration whatsoever after risperidone consumption (170,171).…”
Section: Risperidonementioning
confidence: 99%
“…Further, baseline levels are free of diurnal variations and, according to Pfuhlmann et al [237], independent of sex. Although a positive correlation between CRP and the leukocyte/white blood cell (WBC) count has previously been reported [257], Scherf-Clavel et al discourage the use of WBC count as a measure of inflammation [238]. In their study sample, CRP levels and WBC counts were not significantly associated, and-in contrast to CRP-none of the studied antipsychotic drugs seemed to correlate with the number of leukocytes.…”
Section: Value Of Therapeutic Drug Monitoring During Inflammation-clinical Recommendationsmentioning
confidence: 68%
“…Hefner et al analyzed intraindividual drug and CRP levels (>5 mg/L) of 105 patients and revealed a significant association for the C/D ratio of clozapine and risperidone, but only a trend for quetiapine [40]. Instead, a correlation between pathological CRP concentrations and increases of quetiapine's C/D ratio (n = 166) was shown by Scherf-Clavel et al [238]: the C/D ratio rose by 0.11 (ng/mL)/(mg/day) with each increase of 5 mg/L CRP. A trend was detected for olanzapine (n = 24) while no association to CRP was found for aripiprazole (n = 30) and risperidone (n = 45).…”
Section: Drug Levels Of Antipsychotic Drugs In Relation To Inflammationmentioning
confidence: 99%
See 2 more Smart Citations